Public mediation and intra-procedural conciliation in the province of Tungurahua-Ecuador - Jordan Buenaño, Jeanette; Poaquiza Poaquiza, Patricio (DIXI, 2019)
Objective: Public mediation and intraprocessal conciliation are alternative methods of conflict resolution that allow the parties to end up the legal fight, through dialogue and agreements that benefit those involved in a satisfactory way. This research aims to establish the advance that the public mediation has had in relation to the intraprocesal conciliation within the administration of justice in Tungurahua province, from the year 2014, when the public mediation was established, until the year 2018. Methodology: To do this, an analysis on the use of public mediation and intraprocessal conciliation was done, resulting in the predominance of intra-procedural conciliation as a way to solve the conflict. Results: It is proposed to establish a public policy on the use of mediation in the primary, secondary and university fields, in order to promote mediation as the first option to solve the conflict.